2014
DOI: 10.1111/jfbc.12068
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promoting Components and Related Enzyme Activities of Muskmelon Fruit During its Development and Ripening

Abstract: The present investigation aimed to determine the sugars (reducing, nonreducing) and antioxidants, such as phenols, polyphenols, carotenoids and total antioxidant activity, as well as activities of various enzymes related to these biochemical components in muskmelon at its different developmental stages. The quantity of phenolic compounds (total phenols, total polyphenols) and lycopene was accumulated significantly in ripened stage of muskmelon fruit. The highest levels of activities of sucrose phosphate syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
2
1
0
1
Order By: Relevance
“…The cultivar Stambouli ranks second with 41.3 mg/kg FW. The reported values were in line with our previous results (Henane et al 2016) and are comparable with Menon and Rao (2014) who reported that orange fleshed melon cultivars have higher levels of carotenoid than greenfleshed cultivars. Our results further proved that melon is a significant source of carotenoids (Maieitti et al 2012).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The cultivar Stambouli ranks second with 41.3 mg/kg FW. The reported values were in line with our previous results (Henane et al 2016) and are comparable with Menon and Rao (2014) who reported that orange fleshed melon cultivars have higher levels of carotenoid than greenfleshed cultivars. Our results further proved that melon is a significant source of carotenoids (Maieitti et al 2012).…”
Section: Resultssupporting
confidence: 93%
“…The cultivar Stambouli ranked second with 1080 mg GAE/kg FW. These results are in agreement with those of Menon and Rao (2014) who noticed a substantial amount of phenolic compound in orange-fleshed compared to green-fleshed melon cultivars. Thus, these differences were largely attributed to genotypic variation affecting the melon total phenolic content.…”
Section: Resultssupporting
confidence: 93%
“…The endocarp includes two layers of cells, endocarp a and b. The cells of endocarp a are parenchymatous, and those of endocarp b are elongated and lignified (Menon & Rao, 2014). The functions of the B. napus silique pericarp genes found in this study were consistent with silique structure.…”
Section: Discussionmentioning
confidence: 99%
“…Sugar is a very important carbohydrate in plants and is typically synthesized in the form of sucrose in source leaves, transported to depot tissues, and converted into sucrose, glucose, and fructose through the action of sucrose-metabolizing enzymes for the regulation of material and energy metabolism in cells and continued metabolism and growth [37]. Although the sucrose concentration in sweet cherry is very low, sucrose metabolism plays an important role in sugar metabolism and sucrose metabolism-related enzymes regulate the accumulation of sucrose.…”
Section: Discussionmentioning
confidence: 99%